1964
DOI: 10.1111/j.1469-7998.1964.tb05152.x
|View full text |Cite
|
Sign up to set email alerts
|

The Life History and Reproduction of the Red Kangaroo (Megaleia Rufa)

Abstract: Newborn young of the red kangaroo weighed about 750 mg. They had well‐developed nostrils and a large tongue and the forelimbs and digits of the inanus were well developed but otherwise the external features were embryonic. Sexes of the young were recognized when they were 14 to 20 days old. The young were firmly attached to the teat during the early part of pouch life, but one young removed from the teat at 43 days was able to re‐attach and another was found free when 70 days old. Observations relating to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Continuously breeding macropodid marsupials (kangaroos and wallabies) such as the red kangaroo ( Macropus rufus ) and agile wallaby ( Macropus agilis ) are also capable of “concurrent asynchronous lactation” whereby a female can support the nutritional requirements of two different young at different developmental ages (Sharman & Calaby, 1964; Sharman & Pilton, 1964; Lemon & Barker, 1967; Griffiths, McIntosh & Leckie, 1972; Lincoln & Renfree, 1981). During concurrent asynchronous lactation, adjacent mammary glands can produce milk of very different composition and quantity (Green, Newgrain & Merchant, 1980).…”
Section: True Superfetation In Mammalsmentioning
confidence: 99%
“…Continuously breeding macropodid marsupials (kangaroos and wallabies) such as the red kangaroo ( Macropus rufus ) and agile wallaby ( Macropus agilis ) are also capable of “concurrent asynchronous lactation” whereby a female can support the nutritional requirements of two different young at different developmental ages (Sharman & Calaby, 1964; Sharman & Pilton, 1964; Lemon & Barker, 1967; Griffiths, McIntosh & Leckie, 1972; Lincoln & Renfree, 1981). During concurrent asynchronous lactation, adjacent mammary glands can produce milk of very different composition and quantity (Green, Newgrain & Merchant, 1980).…”
Section: True Superfetation In Mammalsmentioning
confidence: 99%
“…The amorphous material found in the lumen of the lateral vaginae could be related to this function. The lateral vaginae and vaginal sinus produce large amounts of mucus during and shortly after the reproductive period, which enables the sperm to be stored before ovulation (Hughes & Rodger, ; Morgan, ; Rodger, ; Rodger & Bedford, ; Sharmam, , ; Sharmam & Pilton, ). The vaginal sinus epithelium presented PAS‐positive reactivity in the cellular apex indicating the presence of glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Birth in this group often involves the mother sitting on her tail or lower back so that the urogenital sinus is positioned below the pouch. The newborn climbs the intervening distance (perhaps as much as 150 mm in larger macropod diprotodontids like the red kangaroo) up the external wall of the pouch to its rim, before turning downwards into the pouch interior (Beek, ; Poole & Pilton, ; Sharman & Calaby, ; Sharman & Pilton, ; Sharman, ; Tyndale‐Biscoe & Renfree, ; Renfree et al. ; Veitch et al.…”
Section: Discussionmentioning
confidence: 99%
“…Birth in this group often involves the mother sitting on her tail or lower back so that the urogenital sinus is positioned below the pouch. The newborn climbs the intervening distance (perhaps as much as 150 mm in larger macropod diprotodontids like the red kangaroo) up the external wall of the pouch to its rim, before turning downwards into the pouch interior (Beek, 1955;Poole & Pilton, 1964;Sharman & Calaby, 1964;Sharman & Pilton, 1964;Sharman, 1972;Tyndale-Biscoe & Renfree, 1987;Renfree et al 1989;Veitch et al 2000). Our group has already shown that the vestibular apparatus of the newborn tammar (a macropod diprotodontid) has connections with both ipsi-and contralateral vestibular nuclei (McCluskey et al 2008).…”
Section: Comparison Of Vestibular Development Between Different Mammamentioning
confidence: 99%